Implementation of Police Services 110 Integrated Police Service Centers (SPKT Manado Police in Realizing Excellent Service to the Community - Roland Kharis Sejahterawan Baemamenteng (Police Studies Review, 2021)
Technological developments during the industrial revolution 4.0 made the Police create 110 police services as a means of reporting and/or public complaints. However, what happened in the field was that the community had not used the police services in a sustainable manner and even tended to choose another call center. Therefore, the problem formulation of this thesis is how to implement police services 110 and what are the factors that influence the implementation of police services 110. The purpose of this research is to describe the implementation of police services 110 and the factors that influence the implementation of police services 110. This thesis was prepared using a qualitative approach and the type of descriptive analysis research carried out at SPKT Polresta Manado using data collection techniques, interviews, observation, and document review. The results of the research on the implementation of police services to the community are considered to be still not going well because there are still many inhibiting factors such as having double job personnel so that they do not focus on being a monitoring center operator, the operator has never attended training, as well as a complicated bureaucratic system, police services 110 uses pulses, cannot make emergency calls, still affects the credibility of the police service 110. Based on the results of this study, the authors suggest to focus on the duties and functions of personnel so that no double job is involved and then be included in trainings regarding monitoring centers, conducting improvement of reporting flow (bureaucratic system) so that it becomes fast and precise, police service operators are given training and then when carrying out their duties they remain focused on 1 (one) task, re-establish cooperation with third parties to create a free police service 110 credit and can be used for emergency call services, as well as socializing police services 110 continuously.